Tru på Vestlandet Tradisjonar i endring - Løvlie, Birger; Halse, Per; Hatlebrekke, Kristin (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2020)
Religious faith is big part of every day life in Western Norway, both historically and in present time. This book seeks to convey a new understanding of the religious traditions of the region in a time of big cultural change.